A method of predicting effective solvent extraction parameters for recycling of used lubricating oils - Abdul Mutalib, M I (Elsevier Science B.V., 2002)
Solvent extraction technique is one of the cheapest and most efficient processes experienced in recycling of used lubricating oils. In this paper, the performance of three extracting solvents (2-propanol, 1-butanol, and methyl-ethyl-ketone (MEK) in recycling used oil was evaluated experimentally. The effect of the most critical parameters (type of solvent, solvent to oil ratio, and extraction temperature) was investigated. The results show that MEK achieved the best performance with the lowest percent oil losses,followed by 2-propanol and 1-butanol, and as the extraction temperature increases the percent oil losses decreases. The antisolvency energy (Es), which originates from the solubility parameters difference between the solvent and oil was related to the solvent to oil ratio. It was found that the critical clarifying ratio predicted from such relations for the three solvents reasonably agrees with that measured experimentally. Relations between Es and solvent to oil ratio give a proper guideline for preliminary evaluation of the extracting solvent. It also can be used to predict the optimum solvent:oil ratio and extraction temperature based on the solvent ability to dissolve the base oil in used motor oil.